Factors influencing survival in endometrial cancer relapsing patients: a Cooperation Task Force (CTF) study. Issue 4 (1st June 2003) - Sartori, E.; Laface, B.; Gadducci, A.; Maggino, T.; Zola, P.; Landoni, F.; Zanagnolo, V.
Abstract : The purpose of this study was to identify patterns of relapse and to determine the outcome of salvage treatment and the factors influencing survival of endometrial cancer relapsing patients. One thousand six hundred and six endometrial cancer (stages I to IV) patients treated at five Italian institutions were retrospectively reviewed. Of these, 209 (13%) subjects had recurred; the site of relapse was vagina in 35 cases (16.7%), pelvis in 67 (32.1%), and distant locations in 107 (51.2%). Most of the patients relapsed within 24 months: 45% (94) recurred within 1 year, 20.6% (43) between 1 and 2 years. Adjuvant radiotherapy (RT) seemed to reduce the percentage of pelvic recurrence in high risk early stages (IB-IIA) subjects and a higher proportion of patients failed at a distant site when postoperative external-beam pelvic RT was given. However survival curves were not statistically different in the two groups for stage IB endometrial cancer patients. Five and 10-year survival rates of patients with recurrent disease was 26% and 22%, respectively. Relapse of endometrial cancer is often early and at distant sites. Survival rate was related to site of relapse, disease-free interval, and postoperative treatment as independent prognostic variables. The site of relapse is the most important predictor of survival of patients with recurrent disease.